2021
DOI: 10.3390/foods10102310
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of Cricket Chitosan’s Potential as a Prebiotic and a Promoter of Probiotic Microorganisms to Control Pathogenic Bacteria in the Human Gut

Abstract: In this study, cricket chitosan was used as a prebiotic. Lactobacillus fermentum, Lactobacillus acidophilus, and Bifidobacterium adolescentis were identified as probiotic bacteria. Cricket chitin was deacetylated to chitosan and added to either De Man Rogosa and Sharpe or Salmonella/Shigella bacterial growth media at the rates of 1%, 5%, 10%, or 20% to obtain chitosan-supplemented media. The growth of the probiotic bacteria was monitored on chitosan-supplemented media after 6, 12, 24, and 48 h upon incubation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 57 publications
(77 reference statements)
0
19
1
Order By: Relevance
“…These results are similar to those of many previous studies [42,[58][59][60], which demonstrated higher activity of chitosan against Gram-negative than Gram-positive bacteria. This study, however, differs from some previous studies that demonstrated chitosan as having stronger activity against Gram-positive than Gramnegative bacteria [61][62][63][64]. The killing mechanism of chitosan has not yet been well studied, but several postulates have been proposed thus far.…”
Section: Comparative Effects Of the Antimicrobial Activity Of Chitosan From Bsf Shrimp And Conventional Antibiotics Against Selected Pathcontrasting
confidence: 74%
“…These results are similar to those of many previous studies [42,[58][59][60], which demonstrated higher activity of chitosan against Gram-negative than Gram-positive bacteria. This study, however, differs from some previous studies that demonstrated chitosan as having stronger activity against Gram-positive than Gramnegative bacteria [61][62][63][64]. The killing mechanism of chitosan has not yet been well studied, but several postulates have been proposed thus far.…”
Section: Comparative Effects Of the Antimicrobial Activity Of Chitosan From Bsf Shrimp And Conventional Antibiotics Against Selected Pathcontrasting
confidence: 74%
“…The consequences demonstrated that chitosan significantly increased the population of Lactobacillus spp. but decreased that of S. typhimurium [ 114 ]. The prebiotic function of chitin derivatives in inhibiting intestinal pathogenic bacteria can be largely ascribed to the inability of most pathogens to utilize them.…”
Section: The Modulation Of the Gut Microbiota By Chitosan And Cosmentioning
confidence: 99%
“…Colony diameter of the fungus in the dual culture as well as of the test fungus was recorded. Per cent growth inhibition of the pathogen over control was calculated according to the formula given by Kipkoech et al 17 as: where I = % Inhibition; C = Colony diameter in control T = Colony diameter in treatment.…”
Section: Methodsmentioning
confidence: 99%